II. A Practical Philosophy of Religion: A Response to Terrence Tilley’s The Wisdom of Religious Commitment - Johnson, Patricia A. (Philosophy & theology, 1997)
While sympathetic to Tilley’s call for a practical philosophy of religion, I raise three questions: Does Tilley think that one can do philosophy of religion from a position other than that of a committed believer? Does Tilley’s description of the ordinary believer disburden most people from doubt and answerability? Does Tilley’s description of the role of the theologian place too much trust in the theologian? I suggest that some insights from contemporary phenomenology and hermeneutics would lead to a clearer understanding of the role that philosophy of religion can play in the development of a practical philosophy of religion.